2010
DOI: 10.1186/1477-7819-8-1
|View full text |Cite
|
Sign up to set email alerts
|

A pre-operative elevated neutrophil: lymphocyte ratio does not predict survival from oesophageal cancer resection

Abstract: BackgroundElevated pre-operative neutrophil: lymphocyte ratio (NLR) has been identified as a predictor of survival in patients with hepatocellular and colorectal cancer. The aim of this study was to examine the prognostic value of an elevated preoperative NLR following resection for oesophageal cancer.MethodsPatients who underwent resection for oesophageal carcinoma from June 1997 to September 2007 were identified from a local cancer database. Data on demographics, conventional prognostic markers, laboratory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
3
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 40 publications
(42 reference statements)
4
82
3
3
Order By: Relevance
“…In that study, NLR > 9.3 on the first postoperative day correlated with an increased risk of complications. Despite the fact that in the study of Rashid et al (12), it was not found to be a predictive survival parameter for esophageal cancer resection, NLR was a valuable predictive prognostic parameter in other cancer types (3,13,14).…”
Section: Discussionmentioning
confidence: 80%
“…In that study, NLR > 9.3 on the first postoperative day correlated with an increased risk of complications. Despite the fact that in the study of Rashid et al (12), it was not found to be a predictive survival parameter for esophageal cancer resection, NLR was a valuable predictive prognostic parameter in other cancer types (3,13,14).…”
Section: Discussionmentioning
confidence: 80%
“…The anemia encountered in tumor bearing mice is mainly due to reduction in RBC or hemoglobin percentage, and this may occur either due to iron deficiency or due to hemolytic or myelopathic conditions 22 . In EAC control group, a differential count the presence of neutrophils increased, while the lymphocyte count decreased, the observed leucocytopenia indicates a common symptom of immunosuppression in many types of cancers 23,24 and one of the causes of neutrophilia is myeloid growth factors which are produced in malignant process as part of a paraneoplastic syndrome. In addition to this another factor granulocyte colony stimulating factor produced by the malignant cells has also been attributed to be the cause of neutrophilia because of its action on bone marrow granulocytic cells in cancer.…”
Section: Discussionmentioning
confidence: 87%
“…Наряду с этими клетками врож-денного иммунитета большое внимание уделяют Тр, которые относят к иммунорегуляторным клеткам и которые принимают участие не только в процессах гемокоагуляции, тромбоза, адгезии возбудителей, но и в подавлении функции иммунных клеток и стиму-ляции роста опухолей [5]. При количестве Тр более 400х10 9 в 1 л отмечено уменьшение 5-летней ремиссии у больных раком пищевода и, наоборот, уменьшение количества Тр до 200х10 9 в 1 л способствовало увели-чению показателей 5-летней выживаемости больных [5][6][7]. Тр и факторы комплемента играют важную роль в опухользависимом воспалении, привлекая макрофаги и НГ в очаг опухоли [3][4][5].…”
Section: вміст клітин вродженого та набутого імунітету у периферійнійunclassified
“…Иными словами, определенным опухолям головного мозга свойственны разные изменения содержания клеток иммунной системы -Лф и НГ. Значительное увеличе-ние количества Тр в периферической крови у больных с опухолями мозга (400х10 9 в 1 л), как, например, при раке пищевода, мы не выявляли [5,6]. Приведенные результаты могут зависеть в определенной степени от пола и возраста пациентов, наличия сопутствующих заболеваний, размеров и локализации опухоли, для выяснения влияние этих факторов необходимо про-ведение дополнительных исследований на большой когорте пациентов.…”
Section: український нейрохірургічний журнал 2017;(4):38-41unclassified